2013
DOI: 10.1111/cpf.12058
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the reproducibility of the indirect ultrasound method of measuring diaphragm mobility

Abstract: The aim of this study was to assess the reproducibility of the ultrasound (US) measurement of craniocaudal displacement of the left branch of the portal vein as an indirect method of measuring right hemidiaphragm mobility in healthy young adults. Forty-one healthy participants were selected, ranging from 20 to 30 years of age. The US tests were conducted and interpreted by two observers (A and B) on two separate occasions (Test 1 and Test 2). Intra-observer and interobserver reproducibility and repeatability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 33 publications
(71 reference statements)
4
23
0
5
Order By: Relevance
“…This study found a high variability in the amount of diaphragmatic motion (from 30.3 to 96.7 mm), similar to other studies [14, 15, 21]. Kantarci et al [30] found variability of 25 to 84 mm for RH, and of 24 to 81 mm for LH, while in Gerscovich et al [4], variability from 16.7 to 92 mm was found for RH, and 38 to 96 mm for LH.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study found a high variability in the amount of diaphragmatic motion (from 30.3 to 96.7 mm), similar to other studies [14, 15, 21]. Kantarci et al [30] found variability of 25 to 84 mm for RH, and of 24 to 81 mm for LH, while in Gerscovich et al [4], variability from 16.7 to 92 mm was found for RH, and 38 to 96 mm for LH.…”
Section: Discussionsupporting
confidence: 92%
“…There are several imaging methods that assess diaphragmatic mobility: fluoroscopy [1013], ultrasound [14, 15], computed tomography [16], magnetic resonance [1719], and chest radiography [20, 21]. Each technique has its particularities in the observation of the diaphragm, considering cost, radiation exposure and method availability in the study environment [5, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Direct comparison of the absolute reproducibility of DM to our knowledge, have not been investigated. Studies on the reproducibility of DM have shown relative reliability, with ICC value of 0.86 among healthy adults 11 . This values can be compared indirectly with the present study results of ICC value of 0.92 and SEM value of 2.56 which could be considered acceptable for DM measurement using RTUS.…”
Section: Resultsmentioning
confidence: 99%
“…In order to include RTUS as an outcome measure in LBP related trial, it is necessary to establish the reliability of the measurements. Reliability measures of RTUS for assessing DM has been established for healthy young adults 11 . However, the measures of reliability measures are needed for clinical population.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally diaphragm evaluation is accomplished by fluoroscopy (gold pattern); however, ultrasound has shown advantages due to absence of radiation and portability (Boussuges et al, 2009;Nason et al, 2012). Despite the different approaches, either directly attained at the posterior surface of the diaphragm (Kim et al, 2010) or indirectly (craniocaudal displacement of the left branch of the portal vein) (Grams et al, 2014;Yamaguti et al, 2007), there is a consensus that ultrasound is a reproducible and easy to use method (Boussuges et al, 2009;Grams et al, 2014;Kim et al, 2010;Nason et al, 2012).…”
Section: Introductionmentioning
confidence: 99%